2022
DOI: 10.3390/nu14224750
|View full text |Cite
|
Sign up to set email alerts
|

The Synergic Effect of a Nutraceutical Supplementation Associated to a Mediterranean Hypocaloric Diet in a Population of Overweight/Obese Adults with NAFLD

Abstract: Overweight/obesity is often associated with a non-alcoholic fatty liver disease (NAFLD). The study aim was to investigate the effects of a nutraceutical supplementation associated to a Mediterranean-hypocaloric-diet (MHD) on ultrasound-liver-steatosis (ULS) grade improvement in overweight/obese patients with NAFLD. A total of 68 subjects (BMI ≥ 25 kg/m2) with NAFLD were recruited, randomized into 2 groups and treated for 3 months: the Nutraceutical group was treated with MHD plus nutraceutical supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Among them, 253 studies were excluded, including 51 studies in which the control group received other drugs, 16 studies which were non-RCTs, 13 studies in which no indicators were related to NAFLD, 79 studies in which the control group had other liver diseases, 74 studies which were reviews, and 20 studies which had incomplete data. In the end, 43 studies ( Pugh et al, 2013 ; Pugh et al, 2014 ; Abenavoli et al, 2015 ; Hallsworth et al, 2015 ; Dong et al, 2016 ; Panahi et al, 2016 ; Rahmani et al, 2016 ; Zhang et al, 2016 ; Abenavoli et al, 2017 ; Cheng et al, 2017 ; Houghton et al, 2017 ; Manzhalii et al, 2017 ; Misciagna et al, 2017 ; Navekar et al, 2017 ; Panahi et al, 2017 ; Dinu et al, 2018 ; Katsagoni et al, 2018 ; Wong et al, 2018 ; Ahn et al, 2019 ; Cai et al, 2019 ; Chashmniam et al, 2019 ; Ghaffari et al, 2019 ; Ghetti et al, 2019 ; Mirhafez et al, 2019 ; Saadati et al, 2019 ; Campanella et al, 2020 ; Cicero et al, 2020 ; Hariri et al, 2020 ; Nourian et al, 2020 ; Saberi-Karimian et al, 2020 ; Çevik Saldiran et al, 2020 ; Chong et al, 2021 ; Mirhafez et al, 2021 ; Mohamad Nor et al, 2021 ; Alami et al, 2022 ; Asghari et al, 2022 ; Chiurazzi et al, 2022 ; George et al, 2022 ; Khodami et al, 2022 ; Li et al, 2022 ; Mobasheri et al, 2022 ; Yurtdaş et al, 2022 ; Ezpeleta et al, 2023 ) were included in the NMA. The selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 253 studies were excluded, including 51 studies in which the control group received other drugs, 16 studies which were non-RCTs, 13 studies in which no indicators were related to NAFLD, 79 studies in which the control group had other liver diseases, 74 studies which were reviews, and 20 studies which had incomplete data. In the end, 43 studies ( Pugh et al, 2013 ; Pugh et al, 2014 ; Abenavoli et al, 2015 ; Hallsworth et al, 2015 ; Dong et al, 2016 ; Panahi et al, 2016 ; Rahmani et al, 2016 ; Zhang et al, 2016 ; Abenavoli et al, 2017 ; Cheng et al, 2017 ; Houghton et al, 2017 ; Manzhalii et al, 2017 ; Misciagna et al, 2017 ; Navekar et al, 2017 ; Panahi et al, 2017 ; Dinu et al, 2018 ; Katsagoni et al, 2018 ; Wong et al, 2018 ; Ahn et al, 2019 ; Cai et al, 2019 ; Chashmniam et al, 2019 ; Ghaffari et al, 2019 ; Ghetti et al, 2019 ; Mirhafez et al, 2019 ; Saadati et al, 2019 ; Campanella et al, 2020 ; Cicero et al, 2020 ; Hariri et al, 2020 ; Nourian et al, 2020 ; Saberi-Karimian et al, 2020 ; Çevik Saldiran et al, 2020 ; Chong et al, 2021 ; Mirhafez et al, 2021 ; Mohamad Nor et al, 2021 ; Alami et al, 2022 ; Asghari et al, 2022 ; Chiurazzi et al, 2022 ; George et al, 2022 ; Khodami et al, 2022 ; Li et al, 2022 ; Mobasheri et al, 2022 ; Yurtdaş et al, 2022 ; Ezpeleta et al, 2023 ) were included in the NMA. The selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the first definitions of the Mediterranean diet was provided by Willet et al who asserted that the Mediterranean diet reflects the typical eating patterns of some regions of Greece and Italy in the early 1960s, where the adult’s life expectancy was remarkably high, while the rates of diet-related chronic disease were low [ 99 ••]. Several studies, indeed, over the years, have shown that the adoption of the MedDiet can protect against diseases, such as obesity, cardiovascular disease, type 2 diabetes (T2D), and non-alcoholic fatty liver disease (NAFLD) [ 100 , 101 ].…”
Section: Dietary Models and Pcosmentioning
confidence: 99%
“…The beneficial mechanisms of MedDiet involve the reduction of inflammatory and oxidative stress markers and the improvement of lipid profiles, insulin sensitivity, and endothelial function, as well as antiatherosclerotic and antithrombotic properties [ 100 , 101 ]. Furthermore, MedDiet is also considered the best dietary model for the primary prevention of MetS [ 101 ].…”
Section: Dietary Models and Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…Witamina E, L-glutation oraz sylimaryna wykazują działanie przeciwutleniające, przeciwzapalne oraz hepatoprotekcyjne. Wykazano, że stosowanie tych suplementów wraz z dietą śródziemnomorską może stanowić ważny element terapii u pacjentów z NAFLD [28].…”
Section: Dieta śRódziemnomorska a Nafldunclassified